Bio-Efficacy of Glyphosate Ammonium 79.2% SG against Weeds in Tea (Camellia sinensis L.) under Mid-hill Conditions of Himachal Pradesh - Tanha, Said Agha; Chopra, P.; Rana, S. S.; Datt, N.; Singh, G.; Kaur, N. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted at the research farm of Department of Tea Husbandry and Technology, CSK HPKV, Palampur, Himachal Pradesh, India during the summer (February–May) and monsoon (June–October) seasons of 2018. The study consists of ten weed control treatments viz. glyphosate ammonium 79.2% SG at 1.089, 2.178 and 4.356 kg ai ha-1, glyphosate ammonium 71% SG at 2.13 kg ai ha-1, paraquat 0.5 kg ha-1, tank mix combination of glyphosate with 2,4-D (Na) at 1.0+0.5 kg ha-1, glyphosate 1.5 kg ha-1, slashing and in-situ mulching of weeds before flowering, weed free and weedy check. Bidens pilosa, Paspalum distichum, Chromolaena adenophorum, Achyranthus aspera and Artemisia sp., were the dominant weeds in both summer and monsoon seasons. Glyphosate ammonium 79.2% SG at 4.356 kg ai ha-1 being at par with glyphosate 1.00 kg+2,4-D (Na) 0.5 kg ha-1 was quite effective in controlling Bidens pilosa, Paspalum distichum, Chromolaena adenophorum, Achyranthus aspera, Lantana camara, Ageratum sp. and Artemisia sp. in tea. Lowest count of other weeds (Hedera helix, Solanum xanthocarpum, Leucas aspera and Cynodon dactylon) was recorded under glyphosate+2,4-D (Na) 1.0 kg +0.5 kg ha-1 and glyphosate ammonium 79.2% at 4.356 kg ai ha-1, being comparable to weed free check. Among different weed control treatments, significantly higher green leaf yield of 3767 and 3690 kg ha-1 with weed index values of 4.29 and 6.25% was recorded with the application of glyphosate 1.0 kg ha-1+2,4-D (Na) 0.5 kg ha-1 and glyphosate ammonium 79.2% at 2.178 kg ai ha-1, respectively which were also statistically similar to weed free check.